2010
DOI: 10.1080/01621424.2010.511514
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Use of Home-Based Respite Time in Family Caregivers

Abstract: This study investigated the relationship between activities during respite time and depressive symptoms in family caregivers (N = 74) of older adults receiving in-home respite services. Contrary to prior research, demographic contextual variables (caregiver gender, household income, and dyad relationship) and care recipient problems (behavioral dysfunction and functional impairment) were not associated with caregiver depressive symptoms, nor was total minutes engaged in discretionary activities during respite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…Secondly, these efforts and initiatives should be complemented with a dissemination of information on respite care services. Given that studies have found the positive impact of respite care services on caregivers’ quality of life [ 55 ] and depressive symptomatology [ 56 ], these services can provide caregivers with a temporary relief from their caregiving duties to attend relevant activities or handle personal matters. Last but not least, psychoeducation for distressed caregivers can now be understood in the context of the impact of reactions to caregiving on their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, these efforts and initiatives should be complemented with a dissemination of information on respite care services. Given that studies have found the positive impact of respite care services on caregivers’ quality of life [ 55 ] and depressive symptomatology [ 56 ], these services can provide caregivers with a temporary relief from their caregiving duties to attend relevant activities or handle personal matters. Last but not least, psychoeducation for distressed caregivers can now be understood in the context of the impact of reactions to caregiving on their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Na primeira década dos anos 2000, foram publicados dois em 2007 (25,36), 10 em 2008 (18, 21, 26-28, 30, 31, 34, 38, 58) e quatro em 2009 (24,29,35,40). Na segunda década, quatro artigos foram publicados em 2010 (39,44,46,47), oito em 2011 (14,19,23,32,(41)(42)(43)45), três em 2012 (16,37,60), sete em 2013 (15,17,20,22,33,59,61), quatro em 2014 (55)(56)(57)62), três em 2015 (51)(52)(53), três em 2016 (49,50,54), cinco em 2017 (48,63,65,68,70), seis em 2018 (64,66,67,69,71,72), três em 2019…”
Section: Resultsunclassified
“…Consistent with the Stress Process Model of Caregiving, Network members were concerned about the quality of life among family caregivers who prioritize loved ones’ immediate needs before their own. Short-term respite care may ameliorate primary (impaired health, disabilities, limitations) and secondary (role demands, anxiety, depression) stressors among caregivers (Jansen et al, 2009; Mensie & Steffen, 2010; Pearlin, Mullan, Semple, & Skaff, 1990; Robison, Fortinsky, Kleppinger, Shugrue, & Porter, 2009; Schulz & Sherwood, 2008; Tompkins & Bell, 2009).…”
Section: Methodsmentioning
confidence: 99%